2014
DOI: 10.1016/j.jtcvs.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Is the second internal thoracic artery better than the radial artery in total arterial off-pump coronary artery bypass grafting? A propensity score–matched follow-up study

Abstract: The results of our study provide evidence for the superiority of the right internal thoracic artery graft compared with the radial artery as a second conduit in total arterial revascularization off-pump coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…Controversy still remains, on whether the use of the RA as second arterial conduit achieves the same long-term benefits as that documented with the use of the RITA [5][6][7][8][9][10][11][12]. The lack of clear evidence, the potentially increased sternal wound complication rate and the perceived technical complexity by using bilateral internal thoracic arteries often result in the RA as the preferred second conduit of choice [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversy still remains, on whether the use of the RA as second arterial conduit achieves the same long-term benefits as that documented with the use of the RITA [5][6][7][8][9][10][11][12]. The lack of clear evidence, the potentially increased sternal wound complication rate and the perceived technical complexity by using bilateral internal thoracic arteries often result in the RA as the preferred second conduit of choice [1].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a single randomized controlled trial (RCT) [3] has been published in the literature, largely underpowered to detect any difference in long term survival between RITA and RA groups. Several observational studies comparing RITA versus RA have been reported with conflicting findings [5][6][7][8][9][10][11][12]. Propensity score matching (PSM) based analysis of observational data is emerging as an attractive alternative in view of paucity of evidence from RCT, and can be relied upon as evidence when RCTs are not possible [4].…”
mentioning
confidence: 99%
“…64,74,75) Even though they are all muscular arteries, the ITA is more similar in properties to an elastic artery and is resistant to arteriosclerosis and spasms. 66,75,76) However, radial artery and gastroepiploic artery grafts are likely to cause arteriosclerosis and spasms, which are complications characteristic to muscular arteries. Histologically, the radial artery also differs from the ITA in that it has a thicker media comprised of smooth muscle.…”
Section: Radial Arterymentioning
confidence: 99%
“…A number of studies have investigated the patency rate of radial artery grafts, 65,74,76,77) and the results vary. A meta-analysis of five studies showed no remarkable superiority of radial artery grafts over SVGs, due to string phenomenon that occurs with the former.…”
Section: Radial Arterymentioning
confidence: 99%
“…Most recent studies reported better outcomes after use of BITA grafts, especially in the younger population. [1][2][3][4][5] However, some studies reported higher rates of surgical site infection (SSI) after use of BITA grafts because of the decreased blood supply to the sternum and surrounding tissues. [6][7][8] Previous studies investigating the feasibility of using BITA grafts in elderly patients included patients aged >65 or >70 years, [9][10][11][12] but the feasibility of using BITA grafts specifically in octogenarians has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%